Strategic leadership practices as determinants for peak education - Mohd Ali, Hairuddin; Zulkifli, Inas; Ayodele, Lasisi Abass (LAP Lambert Academic Publishing, 2016)
This book is on the practices of strategic leadership among Malaysian Vocational Colleges academic leaders. Besides that, this book also suggests what aspects of strategic leadership are determinants for peak or successful education in these particular colleges in Malaysian context. This book is an inevitable text book for both professional and academics who wish to explore more on the principles and practices of strategic leadership in vocational colleges and how it influence the successful education.